Investigation of indirect (secondary loop) refrigeration systems in commercial food service buildings - Anderson, Chris, author; Bradley, Thomas, advisor; Bandhauer, Todd, committee member; Cross, Jennifer, committee member (Colorado State University. Libraries, 2016)
Indirect (secondary loop) refrigeration systems have recently received increased attention due to their well-known effects on reducing refrigerant losses, particularly in commercial food sales buildings. Although their effects on operating costs, particularly in terms of energy efficiency, are less definitive, there is potential that indirect refrigeration systems might offer significant energy efficiency improvements in food service buildings. The aim of this thesis was to determine the feasibility of an indirect (secondary loop) refrigeration system for a food service building, specifically a Starbucks coffee shop. Six commercial refrigeration units were installed in a laboratory setting. The units were first tested with their air-cooled condensers to establish a baseline. Then, each unit was retrofitted with a water-cooled condenser, and all six water-cooled condensers were connected in series to form a secondary loop system and tested again. The results of this laboratory testing were used to create a predictive model to estimate the payback period for installing the system in different Starbucks coffee shop locations around the country. The model predicted the major requirements for a two year payback period to be high energy costs (>$0.22/kWh), a warm to hot climate (AC runtime > 20 hours per day), and a sufficiently large store (containing multiple large food cases or ice machines).